Prevalence of metabolic syndrome in urban Colombian adolescents aged 10-16 years using three different pediatric definitions (2012)
The aim of this study was to evaluate the metabolic syndrome (MetS) prevalence in adolescents using three different definitions for this age group. The evaluated sample consisted of 718 male and 743 female adolescents. Definitions by Cook et al., de Ferranti et al. and International Diabetes Federation (IDF) for adolescents were used to estimate the prevalence of MetS. The prevalence of MetS was 8.5, 2.5 and 1.2% by de Ferranti et al., Cook et al. and IDF definitions, respectively. High fasting glucose component had the lower prevalence whereas high triglycerides levels component was the most prevalent. In obese adolescents, the prevalence of MetS was higher. MetS classification in adolescents strongly depends on the definition chosen. Further research is required for the evaluation of the current definitions (multicentric studies), and for addition or design of new and useful criteria.